Superradiant cancer hyperthermia using a buckyball assembly of quantum dot emitters - Mallawa Arachchi, S; Premaratne, M; Maini, P (Institute of Electrical and Electronics Engineers, 2018)
With the emergence of nanomedicine, targeted hyperthermia has a high potential of becoming a first-line cancer treatment modality. However, hyperthermia needs to be precisely controlled to avoid damaging adjacent healthy tissues. Due to the uncontrollable transfer of heat from the tumor boundary to healthy tissues, it is extremely difficult to control the temperature increase. As a solution, in this paper, we propose using a superradiant emitter assembly to deliver an ephemeral and powerful thermal pulse to enhance cancer hyperthermia by reducing damage to healthy tissues. Our assembly comprises quantum dot emitters arranged in the shape of a buckyball. We obtain the criteria for our assembly to be superradiant and prove that it is possible to control the superradiance using an external electric field. We analytically obtain expressions for the assembly dynamics and conduct thermal studies using a simple breast cancer model constructed using experimental parameters. Our results indicate that using a series of superradiant pulses can enhance cancer hyperthermia by minimizing the damage to adjacent healthy tissues.